Bodies in Focus: Ten Years of Photographic Practice with Transvestites in Roraima - Martins, Elisangela (Farol, 2025)
This work presents an autoethnography of ten years of photographing alongside a transvestite association in the state of Roraima. It aims to describe the trajectory and understand how photography can contribute to visibility, resistance, and aesthetic-political sharing, drawing on reflections by Jacques Rancière and Judith Butler. It concludes by reflecting on the importance of collective practice, aesthetic experimentation, and affection for the improvement of photographic practice and the political struggles for visibility.